1998
DOI: 10.1039/a815549y
|View full text |Cite
|
Sign up to set email alerts
|

The application of root cultures to problems of biological chemistry

Abstract: Introduction 2 The role of root cultures 3 Production, cultivation and properties of root cultures 4 The range of natural products in root cultures 4.1 General aromatic compounds 4.2 Anthraquinones 4.3 Alkaloids 4.3.1 Pyrrolidine alkaloids 4.3.2 Indole alkaloids 4.3.3 Pyrrolizidine alkaloids 4.3.4 Tropane and related alkaloids 4.3.5 Indolizidine alkaloids 4.3.6 Benzylisoquinoline alkaloids 4.4 Terpenoids and steroids 4.4.1 Sesquiterpenes 4.4.2 Diterpenes 4.4.3 Triterpenes and steroids 4.5 Miscellaneous nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 230 publications
0
3
0
Order By: Relevance
“…45 Robins reported a complete loss of nicotine in the root clones of Nicotiana rustica treated with synthetic auxins. 46 Strikingly, the roots with TK morphology were 100% positive for the TL-and TR-DNA genes. In contrast, the TN roots showed 0% presence of the aux1 and ags genes, and only 16.7% of them were positive for mas1 integration into their genome.…”
Section: Tl-and Tr-dna Integration Into the Genome Of Transgenic Hairmentioning
confidence: 99%
“…45 Robins reported a complete loss of nicotine in the root clones of Nicotiana rustica treated with synthetic auxins. 46 Strikingly, the roots with TK morphology were 100% positive for the TL-and TR-DNA genes. In contrast, the TN roots showed 0% presence of the aux1 and ags genes, and only 16.7% of them were positive for mas1 integration into their genome.…”
Section: Tl-and Tr-dna Integration Into the Genome Of Transgenic Hairmentioning
confidence: 99%
“…In recent years, the use of root organ cultures was found to be efficient for the production of natural compounds, e.g., tropane alkaloids [35]. Thus, hairy root cultures of Datura candida x D. aurea were established after transformation with Agrobacterium rhizogenes strains.…”
Section: Applicationsmentioning
confidence: 99%
“…Several studies using different transformed roots have shown genetic and biochemical stabilities over 10 years (Baiza et al, 1999;Lanoue et al, 2002;Maldonado-Mendoza et al, 1993). Since the mid-1980s, hairy roots have been used as an experimental system for plant root metabolism (Robins, 1998) and also as an alternative to plant cell suspension cultures for the production of fine chemicals (Shanks and Morgan, 1999) on a large scale (Choi et al, 2000;Rhodes et al, 1992). More than 80 plant species have already been transformed with A. rhizogenes (Giri and Narasu, 2000), providing a wide spectrum of applications.…”
Section: Introductionmentioning
confidence: 99%